Optimizing Biology Learning Outcomes: A Group Inquiry-Based Learning Approach Utilizing School Environment - Hernika, Eva; Risnita; Nuraida, Nining (IJER (Indonesian Journal of Educational Research), 2023)
This paper presents a research study that explores how to improve student's learning outcomes by implementing the Group Inquiry-Based Learning Model while making use of the school's surrounding environment in the context of biology learning for grade X science students at Madrasah Aliyah Darud Da'wah Wal-Irsyad Kijang Island. This research adopts the Classroom Action Research (PTK) approach, with data analysis conducted through descriptive analysis. The research findings reveal that implementing the Group Inquiry-Based Learning Model through the utilization of the school's surrounding environment effectively enhances the biology learning outcomes of grade X science students at Madrasah Aliyah Darud Da'wah Wal-Irsyad Pulau Kijang. This improvement is evident in the assessment results across four cycles: pre-cycle, cycle I, cycle II, and cycle III. In the pre-cycle, the research shows an average student learning score of 63.88, with only 8 students or 30% achieving mastery. During cycle I, the average student learning score increases to 70.37, with 12 students, or 44% reaching mastery. In cycle II, the average student learning score further rises to 75.18, with 17 students or 63% achieving mastery. Finally, in cycle III, the average student learning score reaches 81.85, with 23 students or 85% reaching mastery. The research is terminated after cycle III as the learning outcomes meet the mastery criteria. These results collectively demonstrate a consistent improvement in students' learning outcomes, with an overall increase of 55% from the pre-cycle to cycle III.